Will exposure to different consequences of prosocial behavior always lead to subsequent prosocial behavior among adolescents: An experimental study of short videos - Li, Wu; Mao, Yuanyi; Hu, Bo (Frontiers in Psychology, 2022)
The relationship between prosocial media exposure and prosocial behavior has been extensively explored. We explored new dimensions by taking into consideration individuals’ exposure to different consequences of the same prosocial behavior (i.e., reward, punishment, or no consequence) in the context of a new media platform (i.e., the increasingly popular short videos). Drawing upon social cognitive theory and the general learning model, this experimental study aims to identify the effect of exposure to different consequences of prosocial behavior in short videos on subsequent prosocial behavior among adolescents. The study found that the relationship between exposure to the punishment consequence, rather than the reward or no consequences, and prosocial behavior was mediated by moral elevation, while the path of “moral elevation to prosocial behavior” was moderated by empathy. Specifically, moral elevation only positively predicted prosocial behavior among those with low empathy. Based on the experimental study of short videos, our findings uncover the underlying mechanism through which exposure to different consequences of prosocial behavior affects adolescents’ prosocial behavior. The study aslo provides some practical implications for parents and practitioners to nurture prosocial behavior in adolescents.